Binder for ceramic coating diaphragm, preparation method of binder, ceramic coating diaphragm and battery
By designing the adhesive for ceramic coated diaphragm with latex particle structure, the problem of degradation of the adhesion performance of ceramic coated diaphragm under low humidity environment and high temperature and high pressure is solved, and the effect of high temperature heat shrinkage control and high peel strength is achieved. .
Patent Information
- Application Number
- CN202411258163.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-27
AI Technical Summary
The current ceramic-coated diaphragm uses poor thermal stability, resulting in the diaphragm being easily curled in low humidity environments and deteriorating bonding performance under high temperature and high pressure conditions.
The adhesive for ceramic coated separator with latex particle structure, including core layer polymer with softer core and shell polymer with harder shell. The latex particles are formed by a specific polymer monomer and crosslinker ratio design. It can maintain stability under high temperature and high pressure, avoid curling and improve bonding strength.
The ceramic coated separator is controlled within 3% at 150°C. The peeling strength of the separator is high, and it does not curl in low humidity environments. It can firmly adhere the separator and the electrode sheet during the battery hot pressing process to improve the overall polymerization strength. .
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a binder for a ceramic coated diaphragm and a preparation method thereof, a ceramic coated diaphragm, and a battery. Background Art
[0002] As an energy storage device, lithium-ion batteries have the advantages of long cycle life, low self-discharge, high specific energy, and environmental protection, and have been widely used in the field of 3C products. Lithium-ion batteries include diaphragms, which do not directly participate in the electrochemical reaction of the battery, but are an indispensable part of the current liquid lithium-ion batteries. Its main function is to achieve physical isolation between the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other and causing a short circuit. Therefore, the diaphragm should not curl or shrink at high temperatures, which requires the diaphragm to have a certain mechanical strength to withstand the stress during the manufacturing and assembly process, and also requires a certain thermal stability to maintain structural integrity at high temperatures and prevent direct contact between the positive and negative electrodes.
[0003] In order to improve the heat resistance of the diaphragm, the general practice is to apply a ceramic coating on the surface of the base film, wherein the ceramic coating contains a binder. The general diaphragm adhesive uses styrene acrylic or pure acrylic emulsion, which can meet the heat shrinkage of less than 3% at 130°C. PAA type diaphragm adhesive is used at 150°C and above, but due to the introduction of a large number of carboxylic acid groups, it is easy to cause a significant increase in the moisture content of the diaphragm. The high moisture content of the diaphragm is easy to cause curling during the battery winding / unwinding process due to the change from ambient humidity (40%~80%RH) to low humidity (≤3%RH). With the increasing requirements for the energy density of lithium-ion batteries, the thickness of the ceramic diaphragm is constantly shrinking. When the base film is reduced from the previous 9um to 5um, it has become a must to meet the requirements of high temperature resistance of 150°C and avoid curling. Summary of the invention
[0004] In view of the problems that the water-based binder used in the existing ceramic coated diaphragm has poor thermal stability and the diaphragm curls in a low-humidity environment, the present application provides a binder for a ceramic coated diaphragm and a preparation method thereof, a ceramic coated diaphragm, and a battery.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: The present application provides a binder for a ceramic coated diaphragm, the binder comprising latex particles, the latex particles comprising a core layer polymer and a shell layer polymer, the shell layer polymer being arranged on the outer surface of the core layer polymer, the raw material of the core layer polymer comprising a first polymerizable monomer, the raw material of the shell layer polymer comprising a second polymerizable monomer and a third polymerizable monomer, the second polymerizable monomer comprising a polymerizable monomer containing an oxazoline group.
[0006] Preferably, the raw material of the core layer polymer also includes a cross-linking agent. The first polymerizable monomer includes at least one of butyl acrylate, isooctyl acrylate, isobornyl acrylate, styrene, and acrylic acid; The crosslinking agent includes at least one of N-hydroxymethyl acrylamide, vinyl triethoxysilane, vinyl trimethoxysilane acrylate monomer, and silane coupling agent. The weight ratio of the first polymerizable monomer to the crosslinking agent is 100:(0.1-5.0).
[0007] Preferably, the polymerizable monomer containing an oxazoline group comprises vinyl oxazoline; The third polymerizable monomer includes one or more of methacrylic acid, methacrylonitrile, acrylonitrile, methyl methacrylate, methacrylamide, acrylamide, and acrylic acid; The weight ratio of the second polymerizable monomer to the third polymerizable monomer is (0.2-3.0):100.
[0008] Preferably, the glass transition temperature of the core layer polymer is -20°C to 60°C, and the glass transition temperature of the shell layer polymer is greater than 150°C.
[0009] Preferably, the binder further comprises the following raw materials in parts by weight: 0.1 to 0.8 parts of initiator, 0.5 to 2.5 parts of emulsifier, and 50 to 80 parts of water.
[0010] Preferably, the emulsifier is a polymerizable emulsifier, and the polymerizable emulsifier includes at least one of 3-allyloxy-1-hydroxy-1-propane sulfonic acid sodium salt and 2-acrylamido-2-methylpropane sulfonate sodium salt.
[0011] In a second aspect, the present application provides a method for preparing the above-mentioned binder for ceramic coated diaphragms, characterized in that it comprises the following steps: Mixing deionized water, an emulsifier, a first polymerization monomer and a cross-linking agent in a pre-emulsion container to obtain a pre-emulsion; Add deionized water and an emulsifier into a polymerization container and mix them evenly, add the pre-emulsion, and simultaneously drop an initiator to carry out a first polymerization reaction to generate a core layer emulsion containing a core layer polymer; The second polymerizable monomer, the third polymerizable monomer, deionized water, and the emulsifier are pre-emulsified, and then added dropwise with the initiator to the core layer emulsion containing the core layer polymer to carry out a second polymerization reaction, and the binder is obtained after the addition is completed.
[0012] Preferably, the reaction temperature of the first polymerization reaction is 75-90° C., and the reaction time of the first polymerization reaction is 1-3 h; The reaction temperature of the second polymerization reaction is 65-85° C. and the time is 1-4 hours.
[0013] In a third aspect, the present application provides a ceramic coated diaphragm, comprising a base film and a coating layer, wherein the coating layer is obtained by coating a ceramic slurry on at least one side of the base film and drying the coating layer, wherein the ceramic slurry comprises the above-mentioned binder for ceramic coated diaphragms or a binder prepared by the above-mentioned method for preparing the binder for ceramic coated diaphragms.
[0014] In a fourth aspect, the present application provides a battery comprising a positive electrode, a negative electrode and the ceramic coated diaphragm described above.
[0015] Compared with the prior art, the binder for ceramic coated diaphragm provided by the present application, the raw material of the shell polymer includes a second polymerizable monomer, the second polymerizable monomer includes a polymerizable monomer containing an oxazoline group, the glass transition temperature of the prepared latex particle shell polymer is much greater than the glass transition temperature of the core polymer, and the formed latex particles present a structure with a soft core and a hard shell. The binder is mixed with a ceramic material to form a ceramic slurry, and after being coated on the surface of the base film to obtain a ceramic coated diaphragm, the performance of the ceramic coated diaphragm is tested, which can withstand 150°C thermal shrinkage, and its transverse thermal shrinkage and longitudinal thermal shrinkage are both controlled within 3%. The peel strength of the diaphragm is high and the edge is not curled at low humidity. The ceramic coated diaphragm is used in the battery. During the hot pressing process of the battery, the core polymer overflows to achieve bonding. The binder can firmly adhere to the diaphragm and the pole piece. At the same time, the shell is slightly deformed due to extrusion, and the shell polymer particles are close to each other to form a support structure, which can improve the polymerization strength of the entire latex particle, thereby avoiding deformation of the binder under high temperature and high pressure to affect the bonding performance. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] In a first aspect, the present invention provides a binder for a ceramic coated diaphragm, the binder comprising latex particles, the latex particles comprising a core layer polymer and a shell layer polymer, the shell layer polymer being arranged on the outer surface of the core layer polymer, the raw material of the core layer polymer comprising a first polymerizable monomer, the raw material of the shell layer polymer comprising a second polymerizable monomer and a third polymerizable monomer, the second polymerizable monomer comprising a polymerizable monomer containing an oxazoline group.
[0018] The present application provides a binder for ceramic coated diaphragms, the raw material of the shell polymer includes a second polymerizable monomer, the second polymerizable monomer includes a polymerizable monomer containing an oxazoline group, the glass transition temperature of the prepared latex particle shell polymer is much greater than the glass transition temperature of the core polymer, and the formed latex particles present a structure with a soft core and a hard shell. The binder is mixed with ceramic alumina powder / boehmite to form a ceramic slurry, and after being coated on the surface of the base film to obtain a ceramic coated diaphragm, the ceramic coated diaphragm is subjected to a performance test, which can withstand 150°C thermal shrinkage, and its transverse thermal shrinkage and longitudinal thermal shrinkage are both controlled within 3%. The diaphragm has high peel strength and does not curl at low humidity. The ceramic coated diaphragm is used in a battery. During the hot pressing process of the battery, the core polymer overflows to achieve a bonding effect. The binder can firmly adhere to the diaphragm and the pole piece. At the same time, the shell is slightly deformed due to extrusion, and the shell polymer particles are close to each other to form a support structure, which can improve the polymerization strength of the entire latex particle, thereby avoiding deformation of the binder under high temperature and high pressure to affect the bonding performance.
[0019] In some embodiments, the raw material of the core layer polymer further includes a cross-linking agent. The first polymerizable monomer includes at least one of butyl acrylate, isooctyl acrylate, isobornyl acrylate, styrene, and acrylic acid; The crosslinking agent includes at least one of N-hydroxymethyl acrylamide, vinyl triethoxysilane, vinyl trimethoxysilane acrylate monomer, and silane coupling agent; The weight ratio of the first polymerizable monomer to the crosslinking agent is 100:(0.1-5.0).
[0020] Specifically, the weight ratio of the first polymerized monomer to the cross-linking agent is 100:(0.1~5.0), the glass transition temperature of the prepared core layer polymer is in the range of -20~60°C, and the core is relatively soft. During the hot pressing process of the battery, the core polymer overflows to achieve bonding, and the adhesive can firmly adhere to the diaphragm and the electrode.
[0021] The weight ratio of the first polymerizable monomer to the crosslinking agent may be in the following ranges: 100: (0.1-0.5), 100: (0.5-1.0), 100: (1.0-1.5), 100: (1.5-2.0), 100: (2.0-2.5), 100: (2.5-3.0), 100: (3.0-3.5), 100: (3.5-4.0), 100: (4.0-4.5) or 100: (4.5-5.0).
[0022] If the weight ratio of the first polymerized monomer to the cross-linking agent is lower than 100: (0.1~5.0) range, the amount of cross-linking agent added may be too much, or the amount of the first polymerized monomer added may be too little, which affects the proportion of the first polymerized monomer in the polymer chain, increases the glass transition temperature of the generated core layer polymer, and reduces the peeling force of the coated diaphragm; if the weight ratio of the first polymerized monomer to the cross-linking agent is higher than 100: (0.1~5.0) range, the amount of cross-linking agent added may be too little, or the amount of the first polymerized monomer added may be too much, which affects the proportion of the first polymerized monomer in the polymer chain, reduces the electrolyte resistance of the generated core layer polymer, and causes large swelling, which affects the cycle performance.
[0023] Specifically, the first polymerizable monomer and the cross-linking agent are selected from the above-mentioned types, and the first polymerizable monomer and the cross-linking agent undergo a first polymerization reaction under the action of an initiator and an emulsifier to generate a core layer polymer; the generated core layer polymer has a low glass transition temperature and can overflow during the hot pressing process to bond the ceramic coated diaphragm to the positive electrode sheet, and to bond the ceramic coated diaphragm to the negative electrode sheet, thereby improving the bonding strength between the ceramic coated diaphragm and the positive electrode sheet and the negative electrode sheet.
[0024] In some embodiments, the polymerizable monomer containing an oxazoline group includes vinyl oxazoline; The third polymerizable monomer includes one or more of methacrylic acid, methacrylonitrile, acrylonitrile, methyl methacrylate, methacrylamide, acrylamide, and acrylic acid; The weight ratio of the second polymerizable monomer to the third polymerizable monomer is (0.2-3.0):100.
[0025] Specifically, the weight ratio of the second polymerizable monomer to the third polymerizable monomer is in the range of (0.2~3.0):100, the second polymerizable monomer can react with the acid in the third polymerizable monomer to form a cross-linked structure, the glass transition temperature of the prepared shell polymer is much greater than the glass transition temperature of the core polymer, the shell is harder, the shell is slightly deformed due to extrusion, the shell polymer particles are close to each other to form a support structure, which can improve the polymerization strength of the entire latex particles, thereby avoiding deformation of the binder under high temperature and high pressure to affect the bonding performance; the cross-linked structure formed by the reaction of the second polymerizable monomer and the acid in the third polymerizable monomer can reduce the moisture content in the diaphragm, solve the curling problem of the diaphragm from high humidity to low humidity during the battery winding / unwinding process, and improve the heat resistance of the diaphragm.
[0026] If the weight ratio of the second polymerized monomer to the third polymerized monomer is lower than the range of (0.2~3.0):100, the content of the second polymerized monomer is too low, or the content of the third polymerized monomer is too high, the glass transition temperature of the generated shell polymer is low, the hardness of the shell is reduced, and when preparing the ceramic coated diaphragm, the diaphragm is easily curled when rolled up, affecting the normal use of the diaphragm and increasing the cost; at the same time, the heat resistance of the diaphragm is reduced. If the weight ratio of the second polymerized monomer to the third polymerized monomer is higher than the range of (0.2~3.0):100, the content of the second polymerized monomer is too high, or the content of the third polymerized monomer is too low, the hardness of the generated shell polymer is high, affecting the swelling and liquid absorption capacity of the ceramic coated diaphragm, reducing the liquid retention of the battery, and reducing the cycle life of the battery.
[0027] In some embodiments, the glass transition temperature of the core layer polymer is -20°C to 60°C, and the glass transition temperature of the shell layer polymer is greater than 150°C.
[0028] Specifically, the glass transition temperature of the core layer polymer and the glass transition temperature of the shell layer polymer are within the above range, the glass transition temperature of the shell layer polymer is much greater than the glass transition temperature of the core layer polymer, and the formed latex particles present a structure with a softer inner core and a harder outer shell, which prevents the diaphragm from curling under low humidity conditions and solves the problem of diaphragm curling under low humidity conditions; improves the thermal shrinkage performance and peel strength of the ceramic coated diaphragm, and improves the high-temperature adhesion between the ceramic coated diaphragm and the electrode.
[0029] In some preferred embodiments, the glass transition temperature of the core layer polymer is 30°C to 50°C, and the glass transition temperature of the shell layer polymer is greater than 150°C.
[0030] In some embodiments, the weight ratio of the core polymer to the shell polymer is 1:(0.2-5).
[0031] In some embodiments, the binder further comprises the following raw materials in parts by weight: 0.1 to 0.8 parts of an initiator, 0.1 to 1.5 parts of an emulsifier, and 50 to 80 parts of deionized water.
[0032] Specifically, the weight of the initiator can be 0.1, 0.2, 0.3, 0.5, 0.6 or 0.8 parts, as long as the weight of the initiator is within the range of 0.1-0.8 parts, the initiator plays a role in initiating polymerization. The weight of the emulsifier can be 0.5, 0.8, 1.0, 1.5, 1.8, 2.0, 2.2 or 2.5 parts, as long as the weight of the emulsifier is within the range of 0.1-1.5 parts, the emulsifier has the functions of reducing interfacial tension, forming a protective layer on the surface of the droplets, preventing the droplets from aggregating, and emulsifying, etc., which helps to form an emulsion.
[0033] In some embodiments, the emulsifier is a polymerizable emulsifier, and the polymerizable emulsifier includes at least one of 3-allyloxy-1-hydroxy-1-propane sulfonic acid sodium salt and 2-acrylamido-2-methylpropane sulfonate sodium salt.
[0034] The initiator includes at least one of persulfate, azobisisobutyramidine hydrochloride, azobisethylbutyronitrile, benzoyl peroxide and dilauroyl peroxide.
[0035] In a second aspect, the present application provides a method for preparing a binder for a ceramic coated diaphragm, comprising the following steps: Mixing deionized water, an emulsifier, a first polymerization monomer and a cross-linking agent in a pre-emulsion container to obtain a pre-emulsion; Add deionized water and an emulsifier into a polymerization container and mix them evenly, add the pre-emulsion, and simultaneously drop an initiator to carry out a first polymerization reaction to generate a core layer emulsion containing a core layer polymer; The second polymerizable monomer, the third polymerizable monomer, deionized water, and the emulsifier are pre-emulsified, and then added dropwise with the initiator to the core layer emulsion containing the core layer polymer to carry out a second polymerization reaction, and the binder is obtained after the addition is completed.
[0036] Specifically, the pre-emulsion is added, and the initiator is simultaneously added dropwise to carry out the first polymerization reaction. In this step, the pre-emulsion and the initiator can be added in batches, such as first adding 20% of the total mass of the pre-emulsion, and adding a small amount of the initiator at the same time, for a preliminary reaction, and then adding the remaining pre-emulsion and the remaining initiator at the same time for the first polymerization reaction. It is understandable that the entire pre-emulsion can also be directly added, and then the initiator is slowly added dropwise to carry out the first polymerization reaction.
[0037] Pre-emulsifying the second polymerizable monomer, the third polymerizable monomer, deionized water, and the emulsifier specifically refers to uniformly mixing the second polymerizable monomer, the third polymerizable monomer, deionized water, and the emulsifier.
[0038] The present application provides a method for preparing a binder for a ceramic coating diaphragm. The method comprises the following steps: firstly mixing a first polymerizable monomer, the cross-linking agent, the emulsifier, and deionized water to obtain a pre-emulsion; then uniformly mixing the deionized water and the emulsifier, adding the pre-emulsion, and simultaneously dropping an initiator to carry out a first polymerization reaction to obtain a dispersion containing core layer polymer particles; then pre-emulsifying a second polymerizable monomer, a third polymerizable monomer, deionized water, and the emulsifier, and dropping the initiator into the core layer emulsion containing the core layer polymer to carry out a second polymerization reaction to obtain a binder containing latex particles of the core layer polymer and the shell layer polymer. The preparation method is simple, can be completed in only two steps, and is easy to operate.
[0039] In some embodiments, the reaction temperature of the first polymerization reaction is 75-90° C., and the reaction time of the first polymerization reaction is 1-3 h; The reaction temperature of the second polymerization reaction is 65-85° C., and the reaction time of the second polymerization reaction is 1-4 hours.
[0040] Specifically, the first polymerization reaction temperature and time are within the above range, which can generate a core layer polymer with a glass transition temperature in the range of -20°C to 60°C; the second polymerization reaction temperature and time are within the above range, which can generate a shell layer polymer with a glass transition temperature greater than 150°C, thereby obtaining latex particles containing a core layer polymer and a shell layer polymer.
[0041] The polymer synthesized in practice has difficulty in molecular chain rotation due to the use of hard monomers in the shell layer. The glass transition temperature cannot be measured by DSC test, so the glass transition temperature mentioned in this application is a theoretical value calculated using the Fox formula.
[0042] In some embodiments, heating the dispersion containing the core layer polymer particles, the second polymerizable monomer, and the third polymerizable monomer to perform a second polymerization reaction to obtain the binder also includes the following steps: after the second polymerization reaction, adding a neutralizing agent and adjusting the pH value to 6.0~8.0 to obtain the binder.
[0043] The neutralizing agent includes at least one of ammonia water, alkali metal hydroxide, and organic amine compounds.
[0044] In a third aspect, the present application provides a ceramic coated diaphragm, comprising a base film and a coating layer, wherein the coating layer is obtained by coating a ceramic slurry on at least one side of the base film and drying the coating layer, wherein the ceramic slurry comprises the above-mentioned binder for ceramic coated diaphragms or a binder prepared by the above-mentioned method for preparing the binder for ceramic coated diaphragms.
[0045] Specifically, the ceramic slurry is obtained by uniformly mixing a ceramic coating membrane binder, a solvent, and a ceramic material. The ceramic material is commonly used, such as alumina, boehmite, silica, cerium oxide, magnesium aluminum oxide, zirconium oxide, titanium dioxide, and the like.
[0046] The ceramic coated diaphragm provided in the present application can prevent the diaphragm from curling under low humidity conditions during the winding process of the diaphragm, thereby solving the problem of the diaphragm curling under low humidity. The prepared ceramic coated diaphragm can withstand heat shrinkage at 150°C, and its transverse heat shrinkage and longitudinal heat shrinkage are both controlled within 3%. The diaphragm has good heat resistance and high peel strength.
[0047] In a fourth aspect, the present application provides a battery comprising a positive electrode, a negative electrode and the ceramic coated diaphragm described above.
[0048] The battery provided in the present application uses a ceramic coated diaphragm in the battery. During the hot pressing process of the battery, the inner core polymer overflows to achieve a bonding effect. The adhesive can firmly adhere to the diaphragm and the electrode. At the same time, the outer shell is slightly deformed due to extrusion, and the shell polymer particles move closer to each other to form a supporting structure, which can improve the polymerization strength of the entire latex particles, thereby avoiding deformation of the adhesive under high temperature and high pressure and affecting the bonding performance.
[0049] The present invention is further described below by way of examples.
[0050] Example 1 This embodiment provides a method for preparing a binder for a ceramic coating diaphragm, comprising the following steps: S1: Add 200 parts of deionized water, 5 parts of emulsifier 3-allyloxy-1-hydroxy-1-propane sulfonic acid sodium salt, 100 parts each of butyl acrylate and isooctyl acrylate, 120 parts of styrene, 3 parts of acrylic acid, and 2 parts of crosslinking agent silane coupling agent into a pre-emulsion tank, and stir to form a pre-emulsion.
[0051] Add 300 parts of deionized water and 2 parts of emulsifier 3-allyloxy-1-hydroxy-1-propane sulfonic acid sodium salt to the polymerization kettle, stir, heat to 85°C, pump 20 parts of pre-emulsion from the emulsification tank into the polymerization kettle, add 10 parts of 10% ammonium persulfate solution, carry out the first polymerization reaction for 20 minutes, start to uniformly pump in the remaining pre-emulsion and drop 15 parts of 10% ammonium persulfate solution, the pre-emulsion and ammonium persulfate solution are uniformly added to the polymerization kettle within 3 hours to obtain a core layer emulsion containing a core layer polymer. Control the temperature in the polymerization kettle between 83-87°C, and remove the generated heat by cooling water.
[0052] S2: 100 parts of deionized water, 2 parts of emulsifier 3-allyloxy-1-hydroxy-1-propane sulfonic acid sodium salt, 0.2 parts of the second polymerization monomer vinyl oxazoline, 90 parts of the third polymerization monomer methacrylonitrile, and 10 parts of the third polymerization monomer methacrylic acid are mixed and stirred, and after pre-emulsification, 10 parts of 10% ammonium persulfate solution as an initiator are simultaneously added dropwise to the core layer emulsion containing the core layer polymer particles to carry out a second polymerization reaction, which is added dropwise for 1 to 4 hours. After the second polymerization reaction is completed, the binder is obtained.
[0053] The glass transition temperature of the core layer polymer of the binder prepared above is -18°C, the glass transition temperature of the shell layer polymer is 160°C, and the weight ratio of the core layer polymer to the shell layer polymer is 3.25:1.
[0054] Example 2 Most of the steps of this embodiment are the same as those of Embodiment 1, except that, in step S1, the first polymerizable monomer is 60 parts of isooctyl acrylate and 40 parts of isobornyl acrylate, and the cross-linking agent is 1 part of vinyltriethoxysilane; and the weight ratio of the first polymerizable monomer to the cross-linking agent is 100:1.
[0055] In step S2, the second polymerizable monomer is 0.1 parts of vinyl oxazoline, the third polymerizable monomer is 80 parts of acrylonitrile and 20 parts of methyl methacrylate; and the weight ratio of the second polymerizable monomer to the third polymerizable monomer is 0.1:100.
[0056] The prepared binder has a core layer polymer with a glass transition temperature of -20°C, a shell layer polymer with a glass transition temperature of 108°C, and a weight ratio of the core layer polymer to the shell layer polymer of 1:1.
[0057] Example 3 Most of the steps of this embodiment are the same as those of embodiment 1, except that the types of the first polymerizable monomers are 32 parts of butyl acrylate, 88 parts of isobornyl acrylate and 76 parts of styrene, 5 parts of the crosslinking agent vinyl trimethoxysilane acrylate, and the weight ratio of the first polymerizable monomer to the crosslinking agent is 39.2. The prepared adhesive has a glass transition temperature of 60°C for the core layer polymer, and a weight ratio of 2:1 for the core layer polymer to the shell layer polymer.
[0058] Example 4 Most of the steps of this embodiment are the same as those of embodiment 1, except that in step S1, the types of the first polymerizable monomer added are 50 parts of isooctyl acrylate and 0.01 parts of the cross-linking agent N-hydroxymethyl acrylamide.
[0059] The prepared adhesive has a core layer polymer with a glass transition temperature of -30°C, and a weight ratio of the core layer polymer to the shell layer polymer of 1:2.
[0060] Example 5 Most of the steps of this embodiment are the same as those of embodiment 1, except that the types of the first polymerizable monomer are 40 parts of isooctyl acrylate, 60 parts of styrene, and 6 parts of the cross-linking agent vinyltriethoxysilane.
[0061] The prepared adhesive had a core layer polymer having a glass transition temperature of 70°C, and a weight ratio of the core layer polymer to the shell layer polymer of 1:2.5.
[0062] Example 6 Most of the steps of this embodiment are the same as those of embodiment 1, except that in step S2, 3.0 parts of the second polymerizable monomer vinyl oxazoline, 30 parts of the third polymerizable monomer acrylonitrile, 40 parts of methacrylic acid, and 30 parts of methacrylamide are added.
[0063] The glass transition temperature of the core layer polymer of the binder prepared above is -18°C, the glass transition temperature of the shell layer polymer is 168°C, and the weight ratio of the core layer polymer to the shell layer polymer is 3.25:1.
[0064] Comparative Example 1 Use commercially available common diaphragm glue, the composition is styrene acrylic emulsion Comparative Example 2 Use commercially available PAA heat-resistant high-temperature adhesive, the main component of which is a copolymer of acrylic acid and methacrylic acid Comparative Example 3 Most of the steps of this comparative example are the same as those of Example 1, except that in step S2, no second polymerizable monomer is added, and 100 parts of the third polymerizable monomer methyl methacrylate is added.
[0065] The prepared binder has a core layer polymer with a glass transition temperature of -18°C, a shell layer polymer with a glass transition temperature of 100°C, and a weight ratio of the core layer polymer to the shell layer polymer of 3.25:1.
[0066] The binder prepared in the above examples and comparative examples was used with ceramic alumina to prepare a ceramic slurry, with the solid-to-solid ratio of the binder to the ceramic alumina powder being 4.5:100, and then coated on both sides of a 5um PE wet-process base film and dried to obtain a ceramic coated diaphragm. The ceramic coated diaphragms prepared in each example and comparative example were tested as follows.
[0067] Performance Testing: 1) Peel strength test: The ceramic coated diaphragms prepared in the above embodiments and comparative examples were cut into strips of 20 mm*200 mm, and the uncoated side of the diaphragm was tightly bonded to the base plane of the slide, and the coated side was tightly bonded with 3M tape. One end of the pressed sample was fixed with a tensile testing machine, and the 3M tape was pulled at the other end. The tensile testing machine was turned on to perform a peel strength test.
[0068] 2) Thermal shrinkage test: Cut a ceramic coated diaphragm with a side length of about 10 cm and treat it in an electric heated forced air drying oven at 150°C for 30 minutes. Measure the transverse and longitudinal lengths of the diaphragm before and after baking, and calculate the thermal shrinkage rate.
[0069] 3) Curling test: The ceramic coated diaphragm obtained above was placed in an environment with a humidity of 3% RH, and a cross was made on the surface of the diaphragm with a utility knife to observe whether the diaphragm at the cross has curling.
[0070] The above test results are shown in Table 1.
[0071] Table 1 It can be seen from Table 1 that, by comparing Example 1 and Comparative Examples 1-2, the diaphragm glue of Comparative Example 1 adopts styrene-acrylic emulsion, and the prepared diaphragm has high transverse and longitudinal thermal shrinkage rates, and slightly curls under a 3% RH humidity environment; Comparative Example 2 adopts PAA-type heat-resistant high-temperature glue to prepare a diaphragm, although the transverse and longitudinal thermal shrinkage rates are reduced, the diaphragm peel strength is reduced, and the curling problem still exists; This indicates that the ceramic diaphragm prepared by the adhesive provided in the present application can withstand 150°C thermal shrinkage, and its transverse and longitudinal thermal shrinkages are both controlled within 3%, the diaphragm has high peel strength, and does not curl at low humidity.
[0072] Comparing Examples 1 and 6 with Example 2, the glass transition temperature of the shell polymer in Example 2 is lower than 150°C, the transverse and longitudinal thermal shrinkage rates of the ceramic diaphragm are greater than 3%, and it curls slightly in a low humidity environment; comparing Examples 1 and 6 with Comparative Example 3, no second polymer monomer is used in the preparation of the shell polymer, the glass transition temperature of the prepared shell polymer is lower than 150°C, the transverse and longitudinal thermal shrinkage rates of the ceramic diaphragm are greater than 4%, and the diaphragm curls, indicating that when preparing the shell polymer, the second polymer is added, and the weight ratio of the second polymer monomer to the third polymer monomer is (0.2~3.0):100, the acid in the second polymer monomer reacts with the third polymer monomer to form a cross-linked structure, the glass transition temperature of the prepared shell polymer is greater than 150°C, it can withstand thermal shrinkage at 150°C, its transverse and longitudinal thermal shrinkage are both controlled within 3%, the diaphragm has high peel strength, and does not curl at low humidity.
[0073] Comparison between Examples 1 and 3 and Examples 4 and 5 shows that when the weight ratio of the first polymerized monomer to the cross-linking agent is in the range of 100:(0.1~5.0), the glass transition temperature of the prepared core layer polymer is in the range of -20~60°C, the peel strength of the ceramic diaphragm is high, and the ceramic diaphragm does not curl at low humidity.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A binder for ceramic coating diaphragm, characterized in that: The binder includes latex particles, the latex particles include a core layer polymer and a shell layer polymer, the shell layer polymer is arranged on the outer surface of the core layer polymer, the raw material of the core layer polymer includes a first polymerizable monomer, the raw material of the shell layer polymer includes a second polymerizable monomer and a third polymerizable monomer, and the second polymerizable monomer includes a polymerizable monomer containing an oxazoline group.
2. The binder for ceramic coating diaphragm according to claim 1, characterized in that: The raw materials of the core layer polymer also include a crosslinking agent, The first polymerizable monomer includes at least one of butyl acrylate, isooctyl acrylate, isobornyl acrylate, styrene, and acrylic acid; The crosslinking agent includes at least one of N-hydroxymethyl acrylamide, vinyl triethoxysilane, vinyl trimethoxysilane acrylate monomer, and silane coupling agent; The weight ratio of the first polymerizable monomer to the crosslinking agent is 100:(0.1-5.0).
3. The binder for ceramic coating diaphragm according to claim 1, characterized in that: Polymerizable monomers containing oxazoline groups include vinyl oxazoline; The third polymerizable monomer includes one or more of methacrylic acid, methacrylonitrile, acrylonitrile, methyl methacrylate, methacrylamide, acrylamide, and acrylic acid; The weight ratio of the second polymerizable monomer to the third polymerizable monomer is (0.2-3.0):
100.
4. The binder for ceramic coating diaphragm according to claim 1, characterized in that: The glass transition temperature of the core layer polymer is -20°C to 60°C, and the glass transition temperature of the shell layer polymer is greater than 150°C.
5. The binder for ceramic coating diaphragm according to claim 1, characterized in that: The binder further comprises the following raw materials in parts by weight: 0.1-0.8 parts of initiator, 0.5-2.5 parts of emulsifier, and 50-80 parts of water.
6. The binder for ceramic coating diaphragm according to claim 5, characterized in that: The emulsifier is a polymerizable emulsifier, and the polymerizable emulsifier includes at least one of 3-allyloxy-1-hydroxy-1-propane sulfonic acid sodium salt and 2-acrylamide-2-methylpropane sulfonic acid sodium salt.
7. A method for preparing a binder for a ceramic coating diaphragm according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing deionized water, an emulsifier, a first polymerization monomer and a cross-linking agent in a pre-emulsion container to obtain a pre-emulsion; Add deionized water and an emulsifier into a polymerization container and mix them evenly, add the pre-emulsion, and simultaneously drop an initiator to carry out a first polymerization reaction to generate a core layer emulsion containing a core layer polymer; The second polymerizable monomer, the third polymerizable monomer, deionized water, and the emulsifier are pre-emulsified, and then added dropwise with the initiator to the core layer emulsion containing the core layer polymer to carry out a second polymerization reaction, and the binder is obtained after the addition is completed.
8. The method for preparing a binder for a ceramic coating diaphragm according to claim 7, characterized in that: The reaction temperature of the first polymerization reaction is 75-90° C., and the reaction time of the first polymerization reaction is 1-3 hours; The reaction temperature of the second polymerization reaction is 65-85° C. and the time is 1-4 hours.
9. A ceramic coated diaphragm, characterized in that: It includes a base film and a coating layer, wherein the coating layer is obtained by coating a ceramic slurry on at least one side of the base film and drying the coating layer, and the ceramic slurry includes the binder for ceramic coated diaphragms described in any one of claims 1 to 6 or a binder prepared by the preparation method of the binder for ceramic coated diaphragms described in any one of claims 7 to 8.
10. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the ceramic-coated separator according to claim 9.
Citation Information
Cited By
Diaphragm binder, diaphragm and battery
CN120795836A
Diaphragm binder as well as preparation method and application thereof
CN122037835A
Binder, ceramic diaphragm and battery
CN122080817A
